The potential of multicultural congregations in supporting social reconciliation - Naidoo, Marilyn ca. 20./21. Jh. (HTS teologiese studies, 2017)
Race, ethnicity and national identity are important discussions that are unfinished ecclesial business for churches in South Africa. Churches remain mono-cultural to a large extent; a significant challenge is the fact that churches still largely reflect the social divisions of a society. Although not common in South Africa, there are, at the same time, congregations that are successful at reaching across racial and cultural divides to attract new members and build social capital. This article discusses the reconciliation potential of multicultural churches in that they are able to accommodate multiple racial groups, in a society where religious life remains overwhelmingly segregated. Racial integration is a sensitive issue that has divisive potential and churches and religions in general tend to avoid the issue. Religious communities played a critical role in the transition to democracy; what is needed now is for churches to deepen this reconciliation potential.